(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Conditions of inertia-free approximation of equation for vertical velocity of humid atmospheric air at which low inertia of vertical and horizontal motion can be considered are analyzed. The obtained equation can be used in calculating atmospheric processes.